Abnormal paravertebral muscles development is associated with abnormal expression of PAX3 in adolescent idiopathic scoliosis - Qin, Xiaodong; He, Zhong; Yin, Rui; Qiu, Yong; Zhu, Zezhang (European spine journal, 2020)
Purpose The study is aimed to investigate the expression of PAX3 in bilateral paravertebral muscles in adolescent idiopathic scoliosis (AIS) and controls, and to further clarify its association with the paravertebral muscle volume and curve severity. Methods Ten AIS patients and 10 age-matched controls with lumbar disc herniation were included. Bilateral biopsies of paravertebral muscles were obtained at the apical vertebral level for patients and at L5 level for controls. The concave and convex expression of PAX3 was compared between the two groups. The AIS patients were evaluated with magnetic resonance imaging scan of the spine at the apex. The muscle volume of apical paravertebral muscles were measured and compared between concave and convex side. Correlation between concave/convex PAX3 expression ratio and concave/convex muscle volume ratio was analyzed. Results AIS patients were found to have significantly lower PAX3 expression than controls ( p < 0.001). Moreover, PAX3 expression on the concave side was lower than that on the convex side in AIS ( p = 0.003). The muscle volume on the concave side was smaller than convex side as well ( p = 0.001). The PAX3 expression ratio was significantly correlated with the muscle volume ratio ( r = 0.745, p = 0.013); however, there was no significant correlation between PAX3 expression ratio and Cobb angle ( r = 0.284, p = 0.427). Conclusion The PAX3 muscle expression and paravertebral muscle volume were asymmetric in AIS patients, and the expression ratio was positively related with the muscle volume ratio. These findings suggested PAX3 might have functional role in the development of AIS via regulating development of paravertebral muscle. Graphic abstract These slides can be retrieved under Electronic Supplementary Material.